Increased frequency of G-protein β3-subunit 825T allele in dialyzed patients with type 2 diabetes - Blüthner, Martin; Schmidt, Susanne; Siffert, Winfried; Knigge, Heidrun; Nawroth, Peter Paul; Ritz, Eberhard (Kidney international, 1999)
Increased frequency of G-protein β3-subunit 825T allele in dialyzed patients with type 2 diabetes. - Background - A polymorphism (C825T) in exon 10 of the gene encoding the β3 subunit of heterotrimeric G proteins (GNβ3) has recently been described, and the T allele was found to be associated with late-onset hypertension. Because hypertension is a known risk factor for the development of clinically manifest progressive renal disease, we examined the C825T polymorphism in older hemodialysis patients suffering from nondiabetic renal disease or type 2 diabetes with presumed diabetic nephropathy, respectively, and in older healthy controls.